Implementasi Kurikulum Merdeka Melalui Projek Penguatan Pelajar Pancasila SMA Negeri 1 Purwareja Klampok - Linovia Karmelita (Proceedings Series on Social Sciences & Humanities, 2023)
This journal describes the implementation of strengthening pancasila students profile project or P5 at SMA Negeri 1 Purwareja Klampok. The method used in this study was a qualitative research method with a descriptive approach. This study aimed to see how the implementation of the Pancasila student profile program in the independent curriculum, moreover to know whether it had an impact on the formation of student character at school. P5 implementation was applied by combining School Literacy Movement i.e One Class One Book. This program aimed to increase Pancasila values in strengthening pancasila students profile project. These Pancasila values are written in six indicators as Pancasila students reinforcement element. Students who have this profile are students who are fully developed by the six constituent dimensions. These dimensions are: 1) Faith and piety to God Almighty and noble character; 2) Independent; 3) Mutual Cooperation; 4) Global diversity; 5) Critical thinking; 6) Creative. One Class One Book literacy activities were able to realize the profile of Pancasila students, those are having a noble character, having good morals towards humans and the country; global diversity, loves differences; collaborating in a class to make a book according to the agreed theme; creative by producing works in the form of books; critical thinking, able to solve problems and process information; and independent, self-awareness of responsibility for the process and results of learning.